A Framework for Quantifying Resilience to Forest Disturbance - Bryant, Timothy; Waring, Kristen; Sánchez Meador, Andrew; Bradford, John B. (Frontiers in Forests and Global Change, 2019)
The concept of ecological resilience is an invaluable tool to assess the risk of state transitions and predict the impact of management on an ecosystem’s response to future disturbances. However, resilience is difficult to quantify and the factors contributing to resilience are often unknown in systems subject to multiple disturbances. Here, we develop and demonstrate a framework to assess the potential of ponderosa pine and dry mixed conifer forests to be resilient to future disturbance (recover as the same forest type within a managerially significant timeframe) by combining indicators of short-term resilience (ability to withstand disturbance) to fire, insect, and drought disturbances using data from the Rio Tusas-Lower San Antonio landscape in northern New Mexico. The dry mixed conifer forests displayed an average resilience score of 4.54, while ponderosa pine forests had an average score of 3.45 (total possible of nine points) Stand density index was the most important driver of the overall score in the dry mixed conifer type. In the ponderosa pine type, overall basal area was the strongest driver of the overall score. These indicators have the greatest impact on the resilience score and provide the most effective targets for management to increase the possibility of resilience in these forest types. We applied the model in both forest types by comparing individual stands to an ‘ideal’ score for a stand that is within the historic range of variation (HRV) of forest structure for each forest type and confirmed that stands outside of HRV had a low possibility of resilience and stands that had received restoration-based treatments were more likely to be resilient. Our results provide evidence that the changes to forest structure and species composition that have occurred since the onset of fire exclusion have degraded the potential of these forest types to be resilient to future fire, insect, and drought-related disturbances. By modifying disturbances and resilience indicator thresholds this model can be applied to assess resilience to other disturbances within these forest types and across various regions and ecosystem types.